Silicon photonic crystal filter with ultrawide passband characteristics - PEROVA, TANIA; BALDYCHEVA, ANNA (My University, 2011)
We report on what is believed to be the first example of an ultrawide, bandpass filter, based on a high-contrast multicomponent one-dimensional Si photonic crystal (PC). The effect of the disappearance of a limited number of flat stopbands and their replacement with extended passbands is demonstrated over a wide IR range. The passbands obtained exhibit a high transmission of 92% to 96% and a substantial bandwidth of 1800?nm, which is spectrally flat within the passband. The multicomponent PC model suggested can be applied to the design of any micro- or nanostructured semiconductor or dielectric material for application across a wide spectral range.
PUBLISHED
Keywords: Optics; one-dimensional Si photonic crystal (PC); Nanoscience & Materials